Aerosol-Assisted Assembly of Mesoporous Carbon Spheres With Fast and Stable K-ion Storage - Guo, Yu; Li, Jiahui; Wang, Hairui; Chang, Limin; Rui, Binglong; Lin, Li; Xu, Tianhao; Nie, Ping (Frontiers in Chemistry, 2020)
Cost effective anode material with rational design is of significance for rechargeable potassium ion batteries (KIBs). Graphite anode still suffers unfavorable rate capability and moderate cycling stability. In this work, we report a mesoporous carbon sphere with rich porous structure as anode materials for KIBs with the assistance of aerosol spray technology. The as-developed carbon spheres exhibit a well-defined spherical structure with favorable surface area of 1106.32 m2 g-1. Furthermore, the effect of different electrolyte on the electrochemical performance of the carbon anode has been investigated systematically. As expected, the carbon material shows superior potassium storage performance in terms of improved specific capacity of 188.2 mAh g-1, rate capability and prolonged cyclability with a high capacity of 105.3 mAh g-1 after 500 cycles at a rate of 100 mA g-1 toward potassium storage in KFSI based carbonate electrolyte.